Potentiometric and spectrophotometric studies of the complexation of Schiff-base hydrazones containing the pyrimidine moiety - M. SHEBL; S. M. E. KHALIL; B. A. EL-SHETARY; H. S. SELEEM (Journal of the Serbian Chemical Society, 2003)
Three Schiff-base hydrazones (ONN donors) were prepared by condensation of 2-amino-4-hydrazino-6-methylpyrimidine with 2-hydroxyacetophenone, 2-methoxybenzaldehyde and diacetyl to yield 2-OHAHP, 2-OMeBHP and DHP, respectively. The structures of these ligands were elucidated by elemental analysis, UV, IR, 1H-NMR and mass spectra. The metalligand stability constants of Mn2+, Fe3+, Co2+, Ni2+, Cu2+, Zn2+, Cd2+, UO22+ and Th4+ chelates were determined potentiometrically in two different media (75 % (v/v) dioxanewater and ethanolwater) at 283, 293, 303 and 313 K at an ionic strength of 0.05 M (KNO3). The thermodynamic parameters of the 1:1 and 1:2 complexes were evaluated and are discussed. The dissociation constants of 2-OHAHP, 2-OMeBHP and DHP ligands and the stability constants of Co2+, Ni2+ and Cu2+ with 2-OHAHP were determined spectrophotometrically in 75 % (v/v) dioxanewater.